Analisis Kepemimpinan Transformasional dan Motivasi Intrinsik terhadap kinerja karyawan dengan kepuasan kerja sebagai variabel intervening - Agus Destari (UPAJIWA, 2020)
The research was conducted in order to test the variable influence Transformational Leadership and Intrinsic Motivation on Employee Performance through Job Satisfaction at CV. Wiraboga Nusantara Yogyakarta. Was used in this research the independent variable is, Transformational Leadership and Intrinsic Motivation, the dependent variable is Employee Performance, and the intervening variable that is Job Satisfaction.The sampling technique used is census. Samples are employees of CV. Wiraboga Nusantara Yogyakarta, in the 50. The procedure data collection using a questionnaire distributed to be filled by employees. The analysis technique used is path analysis with SPSS 18.0 and SmartPLS 3.2.8. Based analysis of the data and the results of the testing of hypothesis to research it can be concluded that transformational leadership has a positive effect on job satisfaction with a significance level of 0.280. Intrinsic motivation has a positive effect on job satisfaction with a significance level of 0.415. Transformational leadership has a positive effect on employee performance with a significance level of 0.143. Intrinsic motivation has a negative effect on employee performance with a significance level of 0.788. Job satisfaction has a positive effect on employee performance with a significance level of 0,000.